2022
DOI: 10.3390/diagnostics12071663
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Radiomics Texture Features Associated with Increased Coronary Calcium Score—First Results of a Photon-Counting CT

Abstract: The coronary artery calcium score is an independent risk factor of the development of adverse cardiac events. The severity of coronary artery calcification may influence the myocardial texture. Due to higher spatial resolution and signal-to-noise ratio, new CT technologies such as PCCT may improve the detection of texture alterations depending on the severity of coronary artery calcification. In this retrospective, single-center, IRB-approved study, left ventricular myocardium was segmented and radiomics featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…For example, it has been investigated whether PCD-CT might not allow the detection of textural changes in periaortic adipose tissue in relation to the presence of local aortic calcification because of its better spatial resolution and signal-to-noise ratio, and thus possibly provide a biomarker for the development of atherosclerosis 88 . The stability of radiomics features in abdominal VMIs 89 and in the myocardium 90 has been investigated, and it could be shown that some texture alterations of the left ventricular myocardium might be associated with the severity of coronary artery calcification estimated by the Agatston score 91 . We are here only at the beginning of a development whose real potential will become apparent in further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been investigated whether PCD-CT might not allow the detection of textural changes in periaortic adipose tissue in relation to the presence of local aortic calcification because of its better spatial resolution and signal-to-noise ratio, and thus possibly provide a biomarker for the development of atherosclerosis 88 . The stability of radiomics features in abdominal VMIs 89 and in the myocardium 90 has been investigated, and it could be shown that some texture alterations of the left ventricular myocardium might be associated with the severity of coronary artery calcification estimated by the Agatston score 91 . We are here only at the beginning of a development whose real potential will become apparent in further studies.…”
Section: Discussionmentioning
confidence: 99%
“… 88 The stability of radiomics features in abdominal VMIs 89 and in the myocardium 90 has been investigated, and it could be shown that some texture alterations of the left ventricular myocardium might be associated with the severity of coronary artery calcification estimated by the Agatston score. 91 We are here only at the beginning of a development whose real potential will become apparent in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Also due to the novelty of the PCCT scanner and the therefore regularly necessary software updates, the voltage of the scans of the test and the validation collective differed slightly. Nevertheless, other studies in our institution have focused on the impact of the detector type (EICT vs. PCCT) on radiomics analysis of the left ventricular myocardium, outlining a possibly deeper insight into the texture by PCCT ( 30 ). The capability of PCCT of constructing monochromatic reconstructions with different keV could further improve feature stability, especially regarding second order texture features and future studies should focus on exploring the clinical applicability of this aspect ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…89 This indicates the need for further research to properly understand the reasons behind the aforementioned results. Texture features derived from the myocardium scanned with PCD-CT (NAEOTOM Alpha) may have an association with the amount of coronary artery calcification described by Ayx et al 90 Some defined myocardial radiomics-based texture features found to be different between patients with and without coronary artery calcification, resulting in more heterogeneous texture features with increasing Agatston score, which could be due to the possible myocardial fibrosis.…”
Section: Current Evidencementioning
confidence: 99%